COMPARISON OF EXCLUSIVE BREASTFEEDING WITH FORMULA MILK ON THE FREQUENCY OF ACUTE DIARRHEA IN INFANTS AGED 0-6 MONTHS IN PULO ARA GEUDONG TEUNGOH VILLAGE, KOTA DISTRICT THE STRUGGLE OF BIREUEN DISTRICT - Ridha Andria; Atik Badi’ah; Siswanto Pabidang (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Breast milk for babies is the perfect food. This is because of the important antibodies contained in colostrum; in addition, breast milk is also always safe and clean, so it is very unlikely for germs to enter the child's body. Breast milk can protect babies through the various immune substances it contains. Even if the mother is in a state of malnutrition, breast milk still contains sufficient essential nutrients for babies and can overcome infections through phagocyte cell components and immunoglobulins. The purpose of the study: to determine the comparison of the incidence of acute diarrhea in infants with exclusive breastfeeding and formula milk in Pulo Ara Geudong Teungoh Village, Kota Juang District, Bireuen Regency. Method: This study is a Quasi-Experimental study with a pretest-posttest Non-equivalent control group design. The study population was infants aged 0-6 months in Pulo Ara Geudong Teungoh Village, Kota Juang District, Bireuen Regency. The sampling technique was purposive. The sample size was 36 respondents, consisting of 18 people in the exclusive breastfeeding group and 18 people in the formula milk group. During the pretest, the researcher asked about the infant’s history of diarrhea before the treatment. After the treatment, the researcher reassessed the incidence of diarrhea in both groups over a period of one month. Univariate and bivariate data analysis were performed using the Wilcoxon test and the Mann-Whitney test. Results: The results of the Mann-Whitney test analysis show that the Asymp.Sig. (2-tailed) The value is 0.004, which is smaller than 0.05. Therefore, it can be concluded that the hypothesis is accepted, and there is a difference in the incidence of acute diarrhea in infants with exclusive breastfeeding and formula milk. Conclusion: There is a difference in the incidence of acute diarrhea in infants with exclusive breastfeeding and formula milk.